具有扫描阵列光引擎的投影仪 (2021)
一种投影仪组件包括发光二极管(LED)阵列，其中LED阵列具有阵列轴，其中LED阵列包括沿阵列轴布置的多个LED，并且其中多个LED是单独可寻址的。该投影仪组件包括支撑LED阵列的可旋转的致动器，其中可旋转的致动器具有旋转轴，并且其中旋转轴和阵列轴是平行的。该投影仪组件包括：准直器，其被定位成与LED阵列光学通信，用于使从多个LED发射的光准直；以及成像光学器件的组，其被定位成与准直器光学通信，用于聚焦准直光并在一距离处形成LED阵列的第一图像，其中第一图像包括对应于阵列轴的第一轴和与旋转轴正交的第二轴。 A projector assembly includes a light emitting diode (LED) array, wherein the LED array has an array axis, wherein the LED array includes a plurality of LEDs arranged along the array axis, and wherein the plurality of LEDs are individually addressable. The projector assembly includes a rotatable actuator supporting the LED array, wherein the rotatable actuator has a rotation axis, and wherein the rotation axis and the array axis are parallel. The projector assembly includes a collimator positioned in optical communication with the LED array for collimating light emitted from the plurality of LEDs and a set of imaging optics positioned in optical communication with the collimator for focusing collimated light and forming a first image of the LED array at a di